2016
DOI: 10.1155/2016/2986796
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Neuroprotection by Quercetin: Counteracting Oxidative Stress and More

Abstract: Increasing interest has recently focused on determining whether several natural compounds, collectively referred to as nutraceuticals, may exert neuroprotective actions in the developing, adult, and aging nervous system. Quercetin, a polyphenol widely present in nature, has received the most attention in this regard. Several studies in vitro, in experimental animals and in humans, have provided supportive evidence for neuroprotective effects of quercetin, either against neurotoxic chemicals or in various model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
289
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 405 publications
(300 citation statements)
references
References 109 publications
(159 reference statements)
8
289
1
2
Order By: Relevance
“…Recently, quercetin has gained great scientific and clinical interests since it can improve mental/ physical performance and decrease infection risk added to potential benefits to overall health, like anti-carcinogenic, anti-inflammatory, antioxidant, inhibition of lipid peroxidation, platelet aggregation and capillary permeability (Davis, Murphy, & Carmichael, 2009;D'Andrea, 2015). Several clinical trials and animal experimentations have suggested that QR may be a promising natural treatment for both inflammatory skin diseases and neurological diseases either against neurotoxic chemicals or in neurodegenerative diseases (Karuppagounder et al, 2016;Costa, Garrick, Roque, & Pellacani, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, quercetin has gained great scientific and clinical interests since it can improve mental/ physical performance and decrease infection risk added to potential benefits to overall health, like anti-carcinogenic, anti-inflammatory, antioxidant, inhibition of lipid peroxidation, platelet aggregation and capillary permeability (Davis, Murphy, & Carmichael, 2009;D'Andrea, 2015). Several clinical trials and animal experimentations have suggested that QR may be a promising natural treatment for both inflammatory skin diseases and neurological diseases either against neurotoxic chemicals or in neurodegenerative diseases (Karuppagounder et al, 2016;Costa, Garrick, Roque, & Pellacani, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the reduced levels of lipids and decreased lipid oxidation along with reduction in total weight gain, quercetin improved symptoms of histological atherosclerosis in aorta (isolated from male Wistar strain rats). The reduction of oxidative enzyme activity by quercetin was recorded during the Lucio G. Costa experiment (2016‐Hindawi Publishing Corporation) indicating a significant reduction in the ROS level compared to the inflammatory state (Costa, Garrick, Roque, & Pellacani, ). The findings of a research by Paulo Afonso Ribeiro Jorge et al (‐Arquivos Brasileiros de Cardiologia journal) indicated a significant increase in LDL and cholesterol levels as well as plasma MDA and lipid oxidation and formation of atherosclerosis in the aorta (Jorge et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Quercetin has been shown to exert protective effects against cardiovascular diseases like atherosclerosis and ischemia reperfusion-induced injury, as well as anti-cancer and anti-inflammatory effects [12]. Recent studies have also revealed the neuro-protective effects of quercetin in many neurodegenerative diseases such as Alzheimer's disease and Parkinson's disease, and against hypoxiainduced injury and neurotoxic chemical-induced damage [13,14]. However, the mechanisms underlying these effects were not fully understood.…”
Section: Discussionmentioning
confidence: 99%